Penyusunan Regulasi Desa Berdasarkan Undang-Undang Nomor 6 Tahun 2014 Di Kabupaten Indramayu Provinsi Jawa Barat (Institut Pemerintahan Dalam Negeri, 2019)
ABSTRACT The research was conducted in Sidadi Village, Sukajati Village and Wanakaya Village of Haurgeulis Subdistrict, Indramayu District of Wes Java Province. The title of this research is Enactment of Undang-Undang Nomor 6 in 2014 no listed about the village rules, but the law states that regulatory guidelines, the district/city either Regeling or beshicking shall apply mutatis mutandis, so that the village ordinance drafting guidelines also apply mutatis mutandis. Above legislation has been a change from previous rules, so the impact on regulatory guidelines for the village. The author also studies about barriers experienced by the village government, as well as the efforts made by the village government and Indramayu regency government, so the author can write strategy in forming a quality village regulations. Keywords: The formation process and the quality of village regulations regulatory strategy of forming quality village